A high-performance foamed sole material capable of achieving rapid degradation and a preparation method thereof
By using specific proportions of EVA and other materials and foamed sole materials made of degradation-assisted functional masterbatches in footwear products, the environmental protection problems caused by non-degradable plastic materials in existing footwear products are solved, and high performance and rapid degradation effects are achieved.
Patent Information
- Application Number
- CN202310537414.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-12
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2043-05-12
AI Technical Summary
The non-degradable plastic materials in existing footwear products lead to environmental protection problems, and the mechanical properties of environmentally friendly sole materials are poor and have a low degradation rate.
A high-performance foamed sole material is made of kneading and foaming in specific proportions by kneading and foaming of EVA, POE, OBC, SEBS, EPDM, functional masterbatch for degradation, talc, wear-resistant agent, foaming agent, crosslinking agent and active agent. This material can degrade rapidly under specific anaerobic conditions.
It achieves rapid degradation of high-performance foamed sole materials, with the degradation rate within 5 years, and does not affect the mechanical properties in daily use, avoiding plastic pollution, and conforming to the concept of sustainable development.
Smart Images

Figure CN116574323B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of footwear products, and in particular relates to a high-performance foamed sole material capable of achieving rapid degradation and a preparation method thereof. Background Art
[0002] Traditional plastics are organic synthetic polymer materials. Due to the fact that plastics cannot be naturally degraded, they have become mankind’s number one “enemy”. Traditional plastics can exist in the environment for hundreds or even thousands of years, causing damage to the ecological environment and threatening the normal life of organisms.
[0003] As we all know, most of the materials used in general shoe soles are non-degradable organic synthetic polyolefin polymer materials. The surface of polyolefin polymers is hydrophobic, which inhibits the growth of microorganisms. In addition, the structure of polyolefin itself is very stable, so it is difficult to degrade in a short period of time. For example, polyethylene (PE) degrades less than 0.5% in 100 years. Data shows that the global demand for running shoes exceeds 200 million pairs per year, and 80% of sports shoes are eventually thrown into landfills every year. The accumulated discarded sports shoes have brought great difficulties and challenges to the environment, which runs counter to the concept of sustainable development.
[0004] In response to the current environmental protection issues of footwear products, the industry is gradually developing some environmentally friendly sole materials. For example, the Chinese patent document with application number 202010439179.6 discloses an environmentally friendly sole and its manufacturing method, which includes the following steps: ① Mixing, 45% to 55% corn starch, 25% to 35% EVA or rubber or TPU, and 15% to 25% additives are mixed by mass percentage to obtain a mixed material; ② Granulation, the mixed material is placed in a granulator for granulation to obtain mixed material particles; ③ Injection molding and foaming, the mixed material particles are injected into a foaming machine for foaming to obtain a sole embryo; ④ Compression molding, the sole embryo is placed in a mold for compression molding to obtain an environmentally friendly sole. The environmentally friendly sole mainly uses corn starch, which helps to degrade and reduce the pollution of rubber shoe materials.
[0005] However, the current environmentally friendly sports shoes have poor mechanical properties and a low degradation rate due to the large amount of degradable materials such as starch added. Therefore, a high-performance, rapidly degradable foam sole is needed. Summary of the invention
[0006] In view of this, the present invention provides a high-performance foamed sole material that can achieve rapid degradation and a preparation method thereof. The foamed sole provided by the present invention is degradable and can be rapidly degraded under specific anaerobic conditions without affecting its original mechanical properties and other performance.
[0007] The present invention provides a high-performance foamed sole material capable of achieving rapid degradation, which is prepared by mixing and foaming the following raw materials in parts by weight:
[0008] EVA 40-60 parts, POE 0-20 parts, OBC 0-20 parts, SEBS 2-10 parts, EPDM 2-10 parts, degradation-aiding masterbatch 2-4 parts, talc 5-8 parts, wear-resistant agent 0-8 parts, foaming agent 2.5-3.5 parts, cross-linking agent 0.5-0.65 parts, active agent 3-4 parts;
[0009] The degradable functional masterbatch is obtained by blending and granulating a degradable polymer, EVA, a compatibilizer, a coupling agent, an organic acid and its derivatives; the mass ratio of the degradable polymer, EVA, a compatibilizer, a coupling agent, an organic acid and its derivatives is 40-60:20-30:1-5:1-2:15-25.
[0010] Since the publication of Professor Yang Jun of Beijing University of Aeronautics and Astronautics' "Experiment on Rapid Biodegradation of Plastics in the Intestines of Mealworms" in 2014, this discovery has provided a new idea for solving global plastic pollution. In nature, there are a large number of different bacteria / microorganisms in landfills, anaerobic pools in sewage treatment plants, and anaerobic digesters. Some microorganisms can secrete hydrolases and oxidases. The biofilm formed by oxidases on the surface of polyethylene can corrode the plastic surface and generate carbonyls (carbon-oxygen bonds), thereby opening carbon-carbon bonds, and degradation begins, ultimately digesting / decomposing traditional plastics.
[0011] The inventors have found that by adding a biodegradable functional agent to the EVA foam sole, which mainly contains organic components and can be biodegraded by itself; first, the organic matter in the biodegradable functional agent can attract some microorganisms to the surface of the shoe. These organic chemicals promote adenosine triphosphate (ATP) to bring more energy back to the pyruvate (anaerobic) or acetyl-CoA (aerobic) cycle, and produce proteins or lipids from the pyruvate cycle (anaerobic) and acetyl-CoA cycle (aerobic). Secondly, the biodegradable functional agent can enhance the water absorption of the plastic components of the shoe in the microbial-rich environment of an anaerobic landfill, anaerobic sewage pool or anaerobic digester, and at the same time allow the microorganisms to produce a biofilm on the surface of the shoe. This biofilm is formed by the acid and enzyme secreted by the microorganism. The enzyme makes the shoe "hydrophilic", and the resulting biofilm allows the microorganism to hydrolyze the shoe. As the microorganisms secrete enzymes and water, the accumulation of water expands the plastic polymer molecule chain, allowing the microorganism to consume the polymer chain from beginning to end. When microorganisms break down polymers into amino acids, fatty acids and sugars, they secrete signal molecules that attract other microorganisms, creating a feeding effect. Eventually, the microorganisms begin to multiply on the surface of the shoe, help expand the molecular structure, create more space for microorganisms, and send chemical signals on the polymer chain that attract other microorganisms to feed on the shoe, improving the biodegradability and degradation rate of the shoe, allowing the sneakers to decompose naturally within 5 years instead of hundreds of years later.
[0012] In the present invention, the biodegradable functional masterbatch is obtained by blending and granulating a certain proportion of a biodegradable polymer, EVA (ethylene vinyl acetate copolymer), a compatibilizer, a coupling agent, and an organic acid and its derivatives; the mass ratio of the biodegradable polymer, EVA, a compatibilizer, a coupling agent, and an organic acid and its derivatives is 40-60:20-30:1-5:1-2:15-25. The biodegradable functional masterbatch of the present invention has good physical properties. After a small amount of it is added to the foaming sole, it will not affect its original properties, and the shoes will only disintegrate or become brittle under specific anaerobic conditions, and will not degrade in an aerobic environment. Therefore, there is no risk of degradation of the shoes during daily wear and use, which is a first in the industry.
[0013] Preferably, the degradable polymer described in the embodiment of the present invention is a blend of polycaprolactone and polyhydroxyalkanoate, and the ratio of the two can be 5-6:4-5, and the optimal ratio is 6:4. The specific parameters of polycaprolactone include: molecular weight 40,000-80,000, melting point 60°C; polyhydroxyalkanoate is specifically hydroxybutyric acid caproic acid copolyester (PGBHHx), whose molecular weight can be 110,000 and melting point 110°C. The EVA in the raw material for preparing the degradable functional masterbatch includes EVA with VA = 18%-33%, and the preferred varieties are: EVA 265 (DuPont); the compatibilizer is preferably maleic anhydride grafted EVA, which can be conventionally commercially available, such as maleic anhydride grafted EVA with 28% VA content, the grafting rate is 5%, the MI melt index is 1.5g / 10min, and the melting point is 70°C. In addition, the organic acid and its derivatives include stearic acid amine, oleamide, citric acid, salicylic acid, glycolic acid and propionic acid. In addition, the coupling agent may be a titanate coupling agent.
[0014] The preferred degradable functional masterbatch of the present invention is made by mixing a variety of organic substances, and the specific raw materials include: 30 parts of polycaprolactone, 20 parts of polyhydroxyalkanoate, 25 parts of EVA, 5 parts of maleic anhydride grafted EVA, 2 parts of stearic acid amine, 2 parts of salicylic acid, 3 parts of oleic acid amide, 2 parts of citric acid, 5 parts of glycolic acid, 4 parts of propionic acid, and 2 parts of titanate coupling agent. In the preferred embodiment of the present invention, polycaprolactone and polyhydroxyalkanoate, EVA, and maleic anhydride grafted EVA can be first mixed in an internal mixer at 80-90°C for 10-20 minutes, and then stearic acid amine, oleic acid amide, salicylic acid, citric acid, glycolic acid, propionic acid, and titanate coupling agent are added and mixed, and blend A is obtained after 10-20 minutes; thereafter, blend A is granulated by a single screw granulator to obtain a degradable functional agent.
[0015] In a specific embodiment of the present invention, the physical properties of the biodegradable functional masterbatch include: off-white granular shape, density of 0.91-0.93 g / cm 3 , hardness 72A, tensile strength 21MPa, elongation at break 520%, melting point 73°C, melt index MI=3.0g / 10min; and, the degradation rate of the degradable functional masterbatch under anaerobic environment is 45% after 45 days of testing and 98% after 180 days of testing.
[0016] The core of the basic scheme of the embodiment of the present invention is to prepare the above-mentioned degradable functional masterbatch, and then add a small amount (2-4 parts by mass) of it to a certain EVA sole material to obtain a high-performance foamed sole that can be quickly and completely degraded; the foamed sole can degrade the plastic components in the sole in an anaerobic environment through a series of chemical and biological procedures in a microbial manner, and has good usage characteristics.
[0017] In parts by weight, the plastic components in the high-performance foamed sole material described in the embodiment of the present invention include: 40-60 parts of EVA, 0-20 parts of POE, 0-20 parts of OBC, 2-10 parts of SEBS, and 2-10 parts of EPDM.
[0018] Among them, EVA is the English abbreviation of ethylene-vinyl acetate copolymer, which has good strength and elasticity. Compared with polyethylene (PE), EVA introduces vinyl acetate (VA) monomer into the molecular chain, thereby reducing high crystallinity and improving flexibility and impact resistance. Specifically, the mass content of VA in the EVA is 18%-33%, and the preferred variety is EVA265 (DuPont), but is not limited to this brand; its weight parts are 45 parts, 46 parts, 50 parts, 58 parts, etc.
[0019] The specific raw materials of the embodiment of the present invention include 5-18 parts of POE and / or 5-16 parts of OBC; POE is the English abbreviation of polyolefin elastomer, mainly ethylene-octene random copolymer, etc., which has better flexibility and resilience, and has better foaming effect when used with EVA. It can include commercially available POE products with a hardness of 63-88A, and the preferred varieties are: POE 8150 (Dow Company). The full name of OBC is block olefin copolymer, which has an ethylene-octene alternating block structure and has better comprehensive performance than other olefin copolymers; its commercially available products may include a hardness of 50-70A, and the preferred variety is: Infuse 9107 (Dow Company). In the preferred embodiment of the present invention, it further includes 10-15 parts of POE and 10-15 parts of OBC.
[0020] In addition, the embodiment of the present invention also uses 2-10 parts by mass of SEBS and 2-10 parts by mass of EPDM. SEBS is the abbreviation of a linear triblock copolymer with polystyrene as the terminal segment and ethylene-butylene copolymer obtained by hydrogenating polybutadiene as the middle elastic block, and has excellent aging resistance and mechanical properties. The styrene content in the SEBS is preferably less than 35%, that is, it is preferably a styrene-ethylene-butylene-styrene copolymer with a styrene (S) content of less than 35%, such as an S content of 10-30%, and the more preferred variety is SEBS YH688 (Baling Petrochemical Company); its mass content can be 5 parts, 8 parts, or 10 parts.
[0021] The EPDM is the abbreviation of ethylene propylene diene monomer rubber, specifically a terpolymer of ethylene, propylene and non-conjugated diene, expressed as ethylene-propylene-non-conjugated diene terpolymer, the ethylene structure mass content can be 65-70%, and it has high strength; the preferred variety: EPDM626 (Sabik Company). The embodiment of the present invention can specifically use 5 parts, 6 parts or 10 parts of EPDM, and the corresponding commercial products can be used. In the preferred embodiment of the present invention, the mass ratio of the plastic material composition is: EVA 45-50 parts, POE 5-15 parts, OBC 5-15 parts, SEBS 5-10 parts, EPDM 5-10 parts.
[0022] In addition to adding 2-4 parts of the aforementioned degradation-aiding functional masterbatch, the raw materials for preparing the high-performance foamed sole material that can achieve rapid degradation described in the embodiment of the present invention also include, by weight: 5-8 parts of talc, 0-8 parts of wear resistance, 2.5-3.5 parts of foaming agent, 0.5-0.65 parts of cross-linking agent, and 3-4 parts of active agent.
[0023] In the embodiment of the present invention, the talc powder mainly plays a reinforcing filling role, and the preferred particle size is 1000-2000 mesh; that is, it specifically includes 1000-2000 mesh granular talc powder, and the preferred varieties are: BH-1500, and the preferred amount is 5-7 parts by weight. The wear-resistant agent is preferably a silicone wear-resistant agent with a silicone content greater than 50wt%; that is, the wear-resistant agent preferably has a silicone content greater than 50%, and the specific varieties are A-108E (silicone granular wear-resistant agent, Xiamen Baishiyuan Industry and Trade Co., Ltd.), and the wear-resistant agent can be added or not added in the embodiment of the present invention.
[0024] In the embodiment of the present invention, the foaming agent is generally an azo foaming agent, such as AC foaming agent (azodicarbonamide), preferably including a brand with a foaming decomposition temperature of 170-180°C, and the specific variety can be AC 818H. At the same time, the cross-linking agent is mainly a peroxide cross-linking agent, including one of diisopropylbenzene peroxide (also known as vulcanizing agent DCP) and 1,4-di-tert-butyl peroxyisopropylbenzene (also known as BIBP); the preferred variety is: BIBP. In order to enhance the processability such as cross-linking, 3-4 parts of active agents are added in the embodiment of the present invention, generally including: 1.0-1.5 parts of zinc oxide, 1.0-1.1 parts of stearic acid, and 0.9-1.0 parts of zinc stearate, wherein zinc oxide uses a brand with a zinc content greater than 99%, and the preferred variety is ZnO 997. Further preferably, 1.2 parts of zinc oxide, 1.0 parts of stearic acid, and 1.0 parts of zinc stearate.
[0025] Accordingly, an embodiment of the present invention provides a method for preparing the high-performance foamed sole material as described above, comprising the following steps:
[0026] S1, blending the degradable polymer, EVA, compatibilizer, coupling agent and organic acid and its derivatives according to a mass ratio, and then granulating to obtain the degradable functional masterbatch;
[0027] S2. The degradable functional masterbatch, EVA, SEBS, EPDM, talcum powder, wear-resistant agent, foaming agent, cross-linking agent and active agent are mixed and granulated by weight, and then subjected to a foaming process to obtain a high-performance foamed sole material that can achieve rapid degradation.
[0028] The preparation materials and other contents of the degradable functional masterbatch are as described above; in step S1 of the embodiment of the present invention, the blending is preferably carried out in a mixing device at 80-90°C, and then granulated by a single screw granulating device to obtain the degradable functional masterbatch of the present invention. The degradable functional masterbatch has good physical properties. After being added to the foamed sole, it will not only not affect its original properties, but also the shoes will only disintegrate or become brittle under specific anaerobic conditions, and will not degrade in an aerobic environment. Therefore, there is no risk of degradation of the shoes during daily wear and use, which is a first in the industry.
[0029] The preparation of the high-performance sole foam material that can be quickly and completely degraded as described in the embodiments of the present invention can be implemented in a variety of ways, the product has a high yield rate, and can be normally mass-produced.
[0030] Among them, the foaming process described in some embodiments of the present invention is IP foaming, including foaming and baking performed in sequence, and the foaming adopts injection foaming molding equipment. Figure 1 Schematic diagram of the IP process flow for preparing foamed soles in some embodiments of the present invention; Figure 1 As shown, the implementation steps include: weighing, mixing, granulating, foaming and baking.
[0031] According to the dosage of the formula in the specific embodiment of the present invention, BIBP and foaming agent are weighed as the first group; stearic acid, zinc stearate and zinc oxide are weighed as the second group; and the remaining materials are weighed as the third group.
[0032] The mixing process described in the embodiment of the present invention is: first, pour the third group of materials into the internal mixer, turn on the machine, and when the temperature rises to between 80-85°C, pour the second group of materials; when the temperature rises to 90-95°C, pour the third group of materials; when the temperature rises to 100-110°C, pour out the mixed materials.
[0033] Then, the embodiment of the present invention pours the mixed material into the material making machine, and the temperatures of the first, second, third and fourth zones can be adjusted to 75, 80, 85 and 90° C. respectively, and the screw speed is adjusted to 40-50 rpm, and the cutting speed is adjusted to 15-20 rpm.
[0034] The IP foaming preferably includes: pouring the prepared pellets into the injection foaming molding machine, the temperatures of the first, second, third and fourth feeding zones can be adjusted to 80, 85, 90 and 95°C respectively, and the upper and lower mold plate temperatures of the molding mold are adjusted to 170 and 170°C respectively. The material quantity is set according to the mold dosage (such as the mold size is 18cm*10cm*1cm, according to the foaming ratio of 1.5, the material quantity can be set to 120g), the injection time is 200 seconds, and the vulcanization foaming time is 600 seconds. Then, the temperatures of the first, second, third and fourth baking zones are adjusted to 80, 90, 95 and 100°C respectively, and the rotation speed can be 60 rpm; the foamed foaming material is fed into the oven port, and the oven length is preferably 30 meters long; the baking time from beginning to end is preferably 40 minutes.
[0035] In some embodiments of the present invention, the foaming process is MD foaming, including small foaming and compression molding performed in sequence, and the temperatures of the small foaming and compression molding are both 170-175°C. Figure 2 Schematic diagram of the MD process flow for preparing foamed soles in some embodiments of the present invention; Figure 2 As shown, the implementation steps include: weighing, mixing, granulation, small foaming, and secondary compression molding. Among them, the weighing, mixing, granulation and other processes are consistent with the IP process.
[0036] The prepared pellets are subjected to small foaming in a specific embodiment of the present invention: the prepared pellets are poured into a flat-plate compression small foaming mold to complete the first foaming, and the foaming temperature is preferably 173° C.; the foaming time can be 500 seconds.
[0037] The compression molding preferably includes: after the small foamed semi-finished product is cooled for 24 hours, the small foamed semi-finished product is pressed into a flat-plate compression mold to complete the finished product compression; the hot pressing temperature can be 173°C; the hot pressing time is 420 seconds; the cooling water temperature is 25°C and the cooling time is 420 seconds.
[0038] In some other embodiments, the foaming process is supercritical physical foaming, including IP injection, supercritical foaming, and compression molding in sequence; the temperature of the supercritical foaming is 120-160°C. Figure 3 Schematic diagram of the supercritical physical process flow for preparing foamed soles in some embodiments of the present invention; Figure 3 As shown, the implementation steps include: weighing, mixing, granulation, IP injection of small rough embryos, autoclave supercritical foaming, and secondary compression molding.
[0039] According to the dosage of the formula, the specific embodiment of the present invention weighs BIBP as the first group; weighs stearic acid, zinc stearate, and zinc oxide as the second group; and weighs the remaining materials as the third group. The subsequent mixing and granulation processes are consistent with the IP process.
[0040] After the pellets are obtained, the embodiment of the present invention IP injects a small rough embryo: the pellets are poured into the injection foaming molding machine, and the temperatures of the first, second, third, and fourth feeding zones are adjusted to 80, 85, 90, and 95 degrees respectively, and the upper and lower mold plates of the molding mold are adjusted to 170 and 170 degrees respectively. The amount of material is set according to the mold dosage (the mold size is 18cm*10cm*1cm, and the amount of material can be set to 120g according to the foaming ratio of 1.5), the injection time is 200 seconds, the vulcanization time is 600 seconds, and then the small rough embryo of the sole is taken out.
[0041] The autoclave supercritical foaming preferably includes: placing the small rough embryo into an autoclave supercritical physical foaming tank, N2 pressure 20-40MPa, foaming temperature 120-160°C, heat preservation and pressure holding time 1-2h, then releasing the pressure, taking out the foamed sole, and cooling it to room temperature.
[0042] The compression molding preferably includes: after the semi-finished product expanded by supercritical foaming is cooled for 24 hours, it is placed in a flat-plate compression mold to complete the finished product compression; the hot pressing temperature is 173°C; the hot pressing time is 420 seconds; the cooling water temperature is 25°C and the cooling time is 420 seconds.
[0043] The embodiment of the present invention can obtain a high-performance degradable foam sole material, which has good elasticity and flexibility, can be degraded quickly and completely; for example, the density of the high-performance foam sole material is 0.150-0.205g / m 3 The data of biodegradation test are as follows: the degradation rate of the foamed sole is 8.5-9.1% after 45 days of testing under anaerobic environment, 60.1-62.5% after 360 days of testing, and 90.5-94.1% after 3 years of testing. Although the foamed sole is completely degradable, it will not affect its original mechanical properties, and the shoes will only disintegrate or become brittle under specific anaerobic conditions, and will not degrade in an aerobic environment. Therefore, there is no risk of degradation in daily wear and use of the shoes, which is also beneficial to the environment. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] Figure 1 A schematic diagram of the IP process flow for preparing foamed soles in some embodiments of the present invention;
[0045] Figure 2 It is a schematic diagram of the MD process flow for preparing the foamed soles in some embodiments of the present invention;
[0046] Figure 3 Schematic diagram of the supercritical physical process flow for preparing foamed soles according to some embodiments of the present invention. DETAILED DESCRIPTION
[0047] The technical solutions in the embodiments of the present application are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.
[0048] In order to further illustrate and understand the content of the present invention, the preparation method of the present invention is described in detail below in conjunction with the embodiments, but they should not be understood as limiting the scope of protection of the present invention.
[0049] In the following examples, all the raw materials used were commercially available and conventional equipment was used.
[0050] First, 30 parts of polycaprolactone, 20 parts of polyhydroxyalkanoate, 25 parts of EVA, and 5 parts of maleic anhydride grafted EVA were mixed in an internal mixer at 80-90°C for 10 minutes, and then 2 parts of stearic acid amine, 2 parts of salicylic acid, 3 parts of oleic acid amide, 2 parts of citric acid, 5 parts of glycolic acid, 4 parts of propionic acid, and 2 parts of titanate coupling agent were added and mixed. After 10 minutes, blend A was obtained, and blend A was granulated by a single screw granulator to obtain a functional masterbatch for degradability. The specific parameters of polycaprolactone include: molecular weight of 40,000-80,000, melting point of 60°C; polyhydroxyalkanoate is specifically hydroxybutyric acid hexanoic acid copolyester (PGBHHx), with a molecular weight of 110,000 and a melting point of 110°C.
[0051] The general physical properties of the biodegradable functional masterbatch include: off-white granular shape, density of 0.92g / cm 3 , hardness 72A, tensile strength 21MPa, elongation at break 520%, melting point 73°C, melt index MI=3.0g / 10min; and, the degradation rate of the degradable functional masterbatch under anaerobic environment is 45% after 45 days of testing and 98% after 180 days of testing.
[0052] Examples 1-4
[0053] Implementation steps (made with MD process):
[0054] Weighing materials: According to the dosage of the formula in Table 1, weigh BIBP and foaming agent as the first group; weigh stearic acid, zinc stearate, and zinc oxide as the second group; and weigh the remaining materials as the third group.
[0055] Mixing: First, pour the third group of materials into the internal mixer and turn on the machine. When the temperature rises to between 80-85℃, pour in the second group of materials. When the temperature rises to 90-95℃, pour in the third group of materials. When the temperature rises to 100-110℃, pour out the mixed materials.
[0056] Material making: Pour the mixed material into the material making machine, adjust the temperature of the first, second, third and fourth zones to 75, 80, 85 and 90°C respectively, adjust the screw speed to 40-50 rpm, and adjust the cutting speed to 15-20 rpm.
[0057] Small foaming: Pour the prepared pellets into a flat-plate molded small foaming mold to complete the first foaming. The foaming temperature is 173°C and the foaming time is 500 seconds.
[0058] Molding: After the semi-finished product with small foams is cooled for 24 hours, it is pressed into a flat-plate molding mold to complete the finished product molding; the hot pressing temperature is: 173°C; the hot pressing time is: 420 seconds; the cooling water temperature is: 25°C, and the cooling time is: 420 seconds.
[0059] Example 5
[0060] The steps of the embodiment are IP process, and the formula is shown in Table 1;
[0061] The weighing, mixing and granulation of the IP process are the same as those in Example 1. The prepared pellets are poured into the injection foaming machine. The temperatures of the first, second, third and fourth feeding zones can be adjusted to 80, 85, 90 and 95°C, respectively. The upper and lower mold plate temperatures of the molding mold are adjusted to 170 and 170°C, respectively. The amount of material is set according to the amount of the mold (such as the mold size of 18cm*10cm*1cm, according to the foaming ratio of 1.5, the amount of material can be set to 120g), the injection time is 200 seconds, and the vulcanization foaming time is 600 seconds. Then, the temperatures of the first, second, third and fourth zones of the baking partition are adjusted to 80, 90, 95 and 100°C, respectively, and the rotation speed can be 60 rpm; the foamed material is fed into the oven port, and the oven length is selected to be 30 meters long; the baking time from beginning to end is 40 minutes.
[0062] Example 6
[0063] The steps of the embodiment are supercritical physical processes, and the formula is shown in Table 1;
[0064] BIBP is weighed as the first group; stearic acid, zinc stearate and zinc oxide are weighed as the second group; the remaining materials are weighed as the third group. The subsequent mixing and granulation procedures are the same as the IP process.
[0065] Pour the prepared pellets into the injection foaming machine, adjust the temperature of the first, second, third and fourth feeding zones to 80, 85, 90 and 95°C respectively, and adjust the upper and lower mold temperatures to 170 and 170 degrees respectively. Set the material quantity according to the mold dosage (mold size 18cm*10cm*1cm, according to the foaming ratio of 1.5, the material quantity can be set to 120g), the injection time is 200 seconds, the vulcanization time is 600 seconds, and then take out the small rough embryo of the sole, put the small rough embryo into the autoclave supercritical physical foaming tank, N2 pressure 20~40MPa, foaming temperature 120~160°C, keep warm and hold pressure for 1~2h before depressurizing, take out the foamed sole, and cool to room temperature.
[0066] The formula of the comparative example is also shown in Table 1, and the process is the MD process. In addition, the performance test results of each sample are shown in Table 2.
[0067] Table 1 Formula of the embodiment of the present invention
[0068]
[0069] in,
[0070] Biodegradable functional masterbatch: homemade.
[0071] EVA265: hardness 78A, VA content 28%, crystallinity 21.8%, Tg = -20°C, melting point 73°C, DuPont.
[0072] POE 8150: hardness 70A, crystallinity 16%, Tg = -52°C, melting point 55°C, Dow Chemical.
[0073] EPDM626: Mooney viscosity 67 (ML 1+4, 125°C), ethylene content 69%, ENB content 2.8%, Sabic.
[0074] OBC 9107: hardness 60A, crystallinity 13%, Tg = -62°C, melting point 121°C, Dow Chemical.
[0075] SEBS YH688: hardness 43A, S content 13%, star shape, Baling Petrochemical.
[0076] Wear resistant agent A108E: Silicone granular wear resistant agent, Xiamen Baishiyuan Industry and Trade Co., Ltd.
[0077] ZnO 997: Baishi brand zinc oxide, relative density 4.42~4.45, Shanghai Kaiyin Chemical Co., Ltd.
[0078] BIBP: Akzo Nobel.
[0079] Foaming agent AC 818H: Hangzhou Haihong Fine Chemical Co., Ltd.
[0080] Talc BH-1500: 1500 mesh, Quanzhou Xufeng Powder Raw Material Co., Ltd.
[0081] Stearic acid 1801: Dukuda, Indonesia.
[0082] Zinc stearate: Huzhou Linghu Xinwang Chemical Co., Ltd.
[0083] Corn starch: Guangzhou Huayu Biotechnology Co., Ltd.
[0084] Table 2 Comparison of mechanical properties data of implementation cases
[0085]
[0086]
[0087] in conclusion:
[0088] The test results of Comparative Example 1 show that the foamed sole without adding biodegradable materials or degradation-promoting functional agents has all components in its formula as non-degradable materials, and its biodegradation rate in the same period is extremely low, and the biodegradation rate in 3 years is only 7.2%.
[0089] From the test results of Comparative Example 4, it can be seen that after adding 30 parts of corn starch to the sole formula, its biodegradation rate is improved compared with Comparative Example 1, and the biodegradation rate can basically reach 30% within one year, but the biodegradation rate does not change much after one year to three years, because most of the degradable materials in the formula are modified starch materials, and other components are still difficult to degrade. Moreover, after adding corn starch, the performance of the sole is seriously reduced, including comfort, mechanical strength, etc., so it is not suitable for mass production.
[0090] From the test results of Comparative Example 1 and Examples 1-4, it can be seen that by adding different proportions of degradable functional agents, the biodegradation rate is greatly improved, with a 180-day biodegradation rate of >40%, a 360-day biodegradation rate of >60%, and a 3-year biodegradation rate of >90%, indicating that the degradable functional agent can help the non-degradable components in the formula to be effectively degraded, thereby improving the biodegradation rate and degradation rate of the shoes, allowing the sports shoes to decompose naturally within 5 years; and the effect on the mechanical properties of the sole is relatively weak, maintaining the high performance that is basically consistent with that of Comparative Example 1, which is a first in the sports shoe industry.
[0091] From the test results of Comparative Examples 2 and 4 and Examples 1-4, it can be seen that: as the content of the degrading agent increases, the degradation rate in the same period increases accordingly, and adding 2 parts is more effective than adding 1 part, and the degradation rate in the same period increases by 3 times; but after increasing to more than 4 parts, the increase tends to be flat, so the optimal dosage of the degrading agent in the technical solution of the present invention is 2-4 parts.
[0092] From the test results of Examples 3, 5, and 6, it can be seen that for the same matrix formula, whether using the MD secondary molding process, the IP one-shot injection process, or the supercritical physical foaming process, except for slight differences in the mechanical properties of the foamed products, the degradation rate of the foamed products in the same cycle is slightly affected, indicating that the degradation aid functional agent of the present application can be applied to the MD secondary molding process, the IP one-shot injection process, or the supercritical physical foaming process.
[0093] It can be seen from the above embodiments that the foamed sole provided by the embodiments of the present invention is more environmentally friendly. Because the non-degradable part of the existing degradable and environmentally friendly sole cannot be degraded, the non-degradable part will become invisible microplastics after being buried or treated. These microplastics cannot be recycled and will not disappear in nature in a short time. As time goes by, they will circulate in the ocean and soil, and may eventually appear in fish, animals, and even the human body, causing greater harm. The degradable sole of the present invention does not have this hidden danger, and the organic matter in the degradation-aiding functional masterbatch can completely degrade plastics into substances such as carbon dioxide, methane, and water, which is safer and more environmentally friendly.
[0094] Compared with the previous environmentally friendly degradable materials that are only partially degraded, the degradable foamed sole of the present application is a qualitative leap. Compared with the existing environmentally friendly degradable sports shoe soles, the performance of the foamed sole of the present invention will not be affected by the degradation-promoting functional masterbatch and decline, and the original characteristics of the sole are still maintained. Compared with the existing foamed soles added with starch, plant fiber, and degradable polymers, it is more conducive to mass production and is more easily accepted by the market and consumers. Compared with the existing environmentally friendly degradable sports shoe soles, the degradation cycle of the foamed sole of the present invention is shorter, and it can be completely degraded within 3-5 years, while the degradation cycle of the non-degradable part in the existing environmentally friendly degradable soles is as long as several decades or hundreds of years. The existing environmentally friendly degradable soles need to be degraded under specific ambient temperature, humidity, and anaerobic environment. Such harsh conditions are difficult to exist in nature, thereby causing difficulties in degradation. The degradation humidity and temperature of the foamed sole of the present invention are not restricted.
[0095] In addition, the preparation process of the biodegradable functional masterbatch in the present invention is simple and does not require the addition or replacement of equipment. When used, only 2-4 parts need to be added to the EVA foam sole formula to achieve a complete degradation effect on the entire foam sole, and the preparation cost is low.
[0096] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A high-performance foaming sole material capable of achieving rapid degradation, characterized in that: The following raw materials are mixed and foamed by weight: EVA 40-60 parts, POE 10-15 parts, OBC 10-15 parts, SEBS 2-10 parts, EPDM 2-10 parts, degradation-aiding masterbatch 2-4 parts, talc 5-8 parts, wear-resistant agent 0-8 parts, foaming agent 2.5-3.5 parts, cross-linking agent 0.5-0.65 parts, active agent 3-4 parts; The mass content of VA in the EVA is 18%-33%; the mass content of styrene in the SEBS is less than 35%; the hardness of the POE is 63-88A; the hardness of the OBC is 50-70A; the mass content of the ethylene structure of the EPDM is 65-70%; The degradable functional masterbatch is obtained by blending and granulating a degradable polymer, EVA, a compatibilizer, a coupling agent, an organic acid and its derivatives; the mass ratio of the degradable polymer, EVA, a compatibilizer, a coupling agent, an organic acid and its derivatives is 40-60:20-30:1-5:1-2:15-25; the degradable polymer is a blend of polycaprolactone and polyhydroxyalkanoate; the compatibilizer is maleic anhydride grafted EVA; the organic acid and its derivatives include stearic acid amine, oleic acid amide, citric acid, salicylic acid, glycolic acid and propionic acid.
2. The high performance foam sole material according to claim 1, characterized in that: The particle size of the talc powder is 1000-2000 mesh; the anti-wear agent is a silicone anti-wear agent with a silicone content greater than 50wt%; the foaming agent is an azo foaming agent; the cross-linking agent is a peroxide cross-linking agent; the active agent includes: 1.0-1.5 parts of zinc oxide, 1.0-1.1 parts of stearic acid, and 0.9-1.0 parts of zinc stearate.
3. The high performance foamed sole material according to any one of claims 1-2, characterized in that: The density of the high-performance foamed sole material is 0.150-0.205 g / m 3 .
4. The method for preparing the high-performance foamed sole material according to any one of claims 1 to 3, comprising the following steps: S1, blending the degradable polymer, EVA, compatibilizer, coupling agent and organic acid and its derivatives according to a mass ratio, and then granulating to obtain the degradable functional masterbatch; S2. In parts by weight, the degradable functional masterbatch, EVA, POE, OBC, SEBS, EPDM, talcum powder, wear-resistant agent, foaming agent, cross-linking agent, and active agent are mixed and granulated, and then subjected to a foaming process to obtain a high-performance foamed sole material that can achieve rapid degradation.
5. The preparation method according to claim 4, characterized in that: In step S1, the blending is carried out in a mixing device at 80-90°C, and then granulation is carried out by a single screw granulation device.
6. The preparation method according to claim 4, characterized in that: In step S2, the foaming process includes foaming and baking performed in sequence, and the foaming is performed using injection foaming molding equipment.
7. The preparation method according to claim 4, characterized in that: In step S2, the foaming process includes small foaming and compression molding in sequence, and the temperatures of the small foaming and compression molding are both 170-175°C.
8. The preparation method according to claim 4, characterized in that: In step S2, the foaming process includes IP injection, supercritical foaming, and compression molding in sequence; the temperature of the supercritical foaming is 120-160°C.
Citation Information
Patent Citations
Environment-friendly sole and manufacturing method thereof
CN111574753A
Process for the manufacture, according to the Levitherm process, of hard polyvinyl chloride films
EP0000027A1
Universal master batch for anaerobic digestion and degradation and preparation method thereof
CN114085509A
EVA (Ethylene Vinyl Acetate) foaming sole with babysbreath appearance and preparation method thereof
CN114736417A
Cited By
Composite shoe material containing bio-based EVA and preparation method thereof
CN120464057A